Brehe’s Grammar Anatomy - Brehe, Steven (Open textbook library., 2018)
Brehe’s Grammar Anatomy makes grammar accessible to general and specialist readers alike. This book provides an in-depth look at beginner grammar terms and concepts, providing clear examples with limited technical jargon. Whether for academic or personal use, Brehe’s Grammar Anatomy is the perfect addition to any resource library. Features: Practice exercises at the end of each chapter, with answers in the back of the book, to help students test and correct their comprehension Full glossary and index with cross-references Easy-to-read language supports readers at every learning stage